2014
DOI: 10.4314/ejesm.v7i6.6
|View full text |Cite
|
Sign up to set email alerts
|

Trace metal levels of drinking water sources in parts of Osun State, Nigeria

Abstract: (Fe, Mn, Zn, Cu, Cr and Ni) were below or equal to the limits set by WHO for drinking and domestic water while the toxic metals (Pb, Hg, As and Cd), recorded values higher than the safe limits set by WHO hence, the water sources are capable of constituting serious health hazards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Many rural populations also depend on water abstracted from unprotected surface sources such as streams and rivers Afolayan (2018). reported heavy pollution of surface waters in Ibadan with Pb, Cd and Fe, due to the presence of a battery waste dumpsite from which these metals leach to the surface water Odebunmi et al (2014). worked on various ground and surface water samples from different locations in Osun state, and found that the toxic metals (Pb, Hg, As and Cd) were all higher than WHO permissible limit for drinking water.…”
mentioning
confidence: 99%
“…Many rural populations also depend on water abstracted from unprotected surface sources such as streams and rivers Afolayan (2018). reported heavy pollution of surface waters in Ibadan with Pb, Cd and Fe, due to the presence of a battery waste dumpsite from which these metals leach to the surface water Odebunmi et al (2014). worked on various ground and surface water samples from different locations in Osun state, and found that the toxic metals (Pb, Hg, As and Cd) were all higher than WHO permissible limit for drinking water.…”
mentioning
confidence: 99%
“…The studies conducted by Wogu and Okaka (2011), Odebunmi et al (2014), Abubakar (2015, and Sankhla et al (2016) collectively highlight the presence of heavy metal contamination in surface water in Nigeria. Wogu and Okaka (2011) observed high concentrations of iron (Fe) and low concentrations of lead (Pb) in the Warri River, attributed to effluent discharge from the Aladja Iron and Steel Industry.…”
Section: Heavy Metals In Watermentioning
confidence: 99%
“…Wogu and Okaka (2011) observed high concentrations of iron (Fe) and low concentrations of lead (Pb) in the Warri River, attributed to effluent discharge from the Aladja Iron and Steel Industry. Similarly, Odebunmi et al (2014) found elevated levels of lead (Pb), mercury (Hg), arsenic (As), and cadmium (Cd) in drinking water sources in Osun State, exceeding WHOpermitted levels. In contrast, copper (Cu), iron (Fe), chromium (Cr), and zinc (Zn) were within the guidelines.…”
Section: Heavy Metals In Watermentioning
confidence: 99%
“…Arsenic toxicity continues to be a problem because it is difficult to have a global assessment of the burden of arsenic toxicity due to its long latency period and in most cases where water is polluted, there are usually more than one pollutants (Tyler and Allan, 2014;Chitsulo, 2018;UNICEF-WHO, 2018). In Nigeria, studies have shown that the level of arsenic in drinking water (Egbinola and Amanambu, 2014;Odebunmi, et al, 2014;Izah and Srivastav, 2015;Etim, 2017) is higher than the WHO recommended level (10µg/L) (WHO, 2017) with the acceptable limit of 0.01 mg/L recommended by Standard Organization of Nigeria (SON) (Izah and Srivastav, 2015). Arsenic can induce oxidative stress by alternating between oxidation states of metals or by interaction with antioxidants, thereby increasing inflammation, accumulation of free radicals in cells and causing cellular dysfunction (Halliwell and Whiteman, 2004).…”
Section: Introductionmentioning
confidence: 99%